Increased carotid-femoral pulse wave velocity and common carotid artery intima-media thickness obtained to assess target organ damage in hypertensive patients are closely related. (4th July 2019) - Sumbul, Hilmi Erdem; Koc, Ayse Selcan; Demirtas, Derya
ABSTRACT: Background : Increased carotid-femoral pulse wave velocity (CF-PWV) and increased carotid intima-media thickness (IMT) in hypertension (HT) patients are indicators of asymptomatic organ damage. The relationship between carotid IMT and CF-PWV has been shown; studies comparing CF-PWV and IMT values within different vascular regions are limited. We aimed to investigate the relationship between IMT value measured from different anatomical regions and CF-PWV, and the localization of IMT that determines increased CF-PWV best. Methods : This study included 312 patients with HT. CF-PWV measurements with Doppler ultrasonography (USG). Vascular IMTs were measurements of common-internal carotid, brachial, and femoral arteries with B-mode USG (CC-IMT, IC-IMT, B-IMT, and F-IMT, respectively). Patients were divided into two groups according to their CF-PWV value (Increased CF-PWV >10 m/s and normal CF-PWV ≤10m/s). Results : Increased CF-PWV was detected in 54 (17.3%) of HT patients. The patient group with increased CF-PWV was older, and their CC-IMT, IC-IMT and F-IMT values were found to be higher. The other 3 IMT increases excluding B-IMT were closely related to the CF-PWV increase. Only age and CC-IMT values were found to be most closely related to CF-PWV. CC-IMT and age were found to be independently associated with increased CF-PWV. CC-IMT (each-0.1 mm) and age (each year) were found to augment the development of increased CF-PWV by 50.3% and 14.6%, respectively. Conclusion : There is a close relationship between CC-IMT and CF-PWV increase in HT. It was thought that it would still be more useful to look at the increase of CC-IMT compared to other vascular regions for screening asymptomatic organ damage.